(untitled) (World Bulletin of Social Sciences, 2023)
This article outlines the important aspects of tourism brand (in the case of Bukhara region). As well as, it is reflect that it should be taken into account which aspects for creating a Uzbekiston tourism brand and how it can contribute to the development of tourism. In addition, it has information about the tourism potential of Uzbekistan related to creating the Ziyarah tourism brand.